1995
DOI: 10.1017/s0952523800009494
|View full text |Cite
|
Sign up to set email alerts
|

Ontogeny of the opioid growth factor, [Met5]-enkephalin, and its binding activity in the rat retina

Abstract: The endogenous opioid peptide [Met5]-enkephalin is a tonically active opioid growth factor (OGF) with an inhibitory action on DNA synthesis in the developing rat retina. In this study, the ontogeny of the spatial and temporal expression of OGF and its binding activity was examined. OGF-like immunoreactivity was detected in the retina at gestation day (E) 20, but not at E18, and was localized to ganglion cell and neuroblast layers; immunochemical reaction was no longer seen in the retina by postnatal day 6. Nat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

1
3
0

Year Published

1996
1996
2024
2024

Publication Types

Select...
4
2

Relationship

1
5

Authors

Journals

citations
Cited by 14 publications
(4 citation statements)
references
References 56 publications
1
3
0
Order By: Relevance
“…Retinal neuroblasts which are migrating, synthesizing DNA, and dividing within the confines of the NB appear to produce OGF, since radiolabel corresponding to PPE mRNA in the present study, as well as OGF immunoreactivity was found throughout the NB during early postnatal life (Isayama et al, 1995). Therefore, the presence of PPE mRNA in the NB, composed of both dividing and differentiating cells, suggests that neuroblast cells produce OGF in an autocrine manner.…”
Section: Discussionsupporting
confidence: 55%
See 3 more Smart Citations
“…Retinal neuroblasts which are migrating, synthesizing DNA, and dividing within the confines of the NB appear to produce OGF, since radiolabel corresponding to PPE mRNA in the present study, as well as OGF immunoreactivity was found throughout the NB during early postnatal life (Isayama et al, 1995). Therefore, the presence of PPE mRNA in the NB, composed of both dividing and differentiating cells, suggests that neuroblast cells produce OGF in an autocrine manner.…”
Section: Discussionsupporting
confidence: 55%
“…Previous immunocytochemistry, HPLC, and functional experiments have established that the endogenous opioid peptide, [Met 5 ]-enkephalin, is an OGF related to the regulation of DNA synthesis in the developing mammalian retina (Isayama et al, , 1995. In addition, binding activity for the OGF has also been detected in the developing rat retina using in vitro receptor autoradiography with radiolabeled [Met 5 ]-enkephalin (Isayama et al, , 1995. Thus, the presence of gene expression for the OGF precursor during late prenatal and early postnatal life coincides with the time period when OGF is known to function during retinal development, and when the presence of OGF and its binding activity are present.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations